High-capacity and high-compaction lithium iron phosphate as well as preparation method and application thereof

By using a dispersant to coat the particle surface and mixing materials during the grinding stage of lithium iron phosphate, the problem that lithium iron phosphate is difficult to have high compaction density and high specific capacity at the same time is solved, and its electrochemical performance is improved.

CN119706779APending Publication Date: 2025-03-28HENAN LONGBAI NEW MATERIAL TECH CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411888070.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

It is difficult for lithium iron phosphate positive electrode materials to have high compaction density and high specific capacity at the same time, resulting in limited application in lithium-ion batteries.

Method used

By coating the particle surface with a dispersant during the grinding stage, the particle size is reduced, and the material using the dispersant is mixed with the material without the dispersant is not used, the compaction density of the mixed material is increased.

Benefits of technology

Lithium iron phosphate with high specific capacity under high compaction density is achieved, which improves its electrochemical performance and reduces the risk of overfired during calcination.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005200104490000111
    Figure BDA0005200104490000111
  • Figure BDA0005200104490000121
    Figure BDA0005200104490000121
Patent Text Reader

Abstract

The invention provides high-capacity and high-compaction lithium iron phosphate as well as a preparation method and application thereof, and relates to the technical field of lithium ion batteries. Specifically, an iron source, a lithium source, a carbon source, a dispersing agent, an additive and water are mixed and ground, and a first spray material is obtained after spray drying; mixing and grinding a second iron source, a second lithium source, a second carbon source, a second additive and water, and performing spray drying to obtain a second spray material; fully mixing the two spraying materials, calcining and crushing to obtain lithium iron phosphate; wherein the dispersing agent is prepared from one of polyurethane, polyaspartic acid or a polyhydric alcohol-polyethylene imine block copolymer. According to the preparation method, by introducing the specific dispersing agent, the phenomenon of over-burning fusion can be effectively avoided, and a small-particle material with uniform size is obtained, so that the electrochemical performance is improved; and the mixture is mixed with the spraying material without the dispersing agent, so that the compaction density is effectively improved, and the high-capacity and high-compaction lithium iron phosphate is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a high-capacity and high-density lithium iron phosphate and a preparation method and application thereof. Background Art

[0002] Lithium iron phosphate (LiFePO4), also known as LFP (Lithium Iron Phosphate) cathode material, is a cathode active material used in lithium-ion batteries. Lithium iron phosphate has the characteristics of high safety and high stability and has attracted widespread attention. It is mainly used in the fields of power batteries and energy storage batteries, especially in electric vehicles and energy storage systems. At present, most of the batteries installed in new energy vehicles are lithium iron phosphate batteries; and with the rapid development of electric vehicles and energy storage systems, the market demand for lithium iron phosphate cathode materials continues to grow. At the same time, with the innovation of technology and the continuous development of demand, the requirements for the capacity and compaction of lithium iron phosphate are also getting higher and higher.

[0003] The true density of lithium iron phosphate is 3.6g / cm 3 However, due to the existence of voids between particles, voids inside particles and carbon, the compacted density is much lower than 3.6 g / cm in actual use. 3 In the process of preparing lithium iron phosphate, calcining at high temperature can obtain a higher compaction density, but the electrical properties are poor; calcining at a lower temperature can reduce the degree of overburning and improve the electrical properties, but the compaction density is reduced; the compaction density and electrical properties of lithium iron phosphate are difficult to balance. If the high specific capacity of lithium iron phosphate can be maintained at a high compaction density, it will provide a broader development prospect for lithium iron phosphate.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The first object of the present invention is to provide a method for preparing high-capacity and high-compacted lithium iron phosphate, which is used to solve the technical defect that lithium iron phosphate positive electrode materials are difficult to have both high compaction density and specific capacity performance.

[0006] The second object of the present invention is to provide lithium iron phosphate prepared by the preparation method of high-capacity and high-density lithium iron phosphate.

[0007] A third object of the present invention is to provide a lithium ion battery.

[0008] A fourth object of the present invention is to provide an electrical device.

[0009] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0010] A method for preparing high-capacity and high-density lithium iron phosphate comprises the following steps:

[0011] (1) mixing and grinding an iron source, a phosphorus source, a lithium source, a carbon source, a dispersant, an additive and water, and spray drying to obtain a first spray material;

[0012] (2) mixing and grinding a second iron source, a second phosphorus source, a second lithium source, a second carbon source, a second additive and water, and spray-drying the mixture to obtain a second spray material;

[0013] (3) fully mixing the first spray material and the second spray material, calcining and crushing to obtain lithium iron phosphate;

[0014] Wherein, the dispersant includes one of polyurethane, polyaspartic acid or polyol-polyethyleneimine block copolymer.

[0015] A lithium iron phosphate is prepared according to the preparation method of high-capacity and high-density lithium iron phosphate.

[0016] A lithium-ion battery comprises the lithium iron phosphate.

[0017] An electrical device comprises the lithium-ion battery.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] The present invention provides a preparation process route of lithium iron phosphate. By using a dispersant to coat the surface of particles in the grinding stage to reduce the particle size, the phenomenon of over-burning and melting during the calcination process can be effectively avoided, small particles of uniform size can be obtained, the migration distance of lithium ions can be effectively shortened, and the electrochemical performance of the material can be improved. The material using the dispersant is mixed with the material not using the dispersant in the grinding stage, which effectively increases the compaction density of the mixed material. Compared with the case where the dispersant is not introduced, lithium iron phosphate with both high capacity and high compaction can be obtained when calcined at the same temperature. DETAILED DESCRIPTION

[0020] The technical scheme of the present invention will be clearly and completely described below in conjunction with specific embodiments, but those skilled in the art will appreciate that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. Those who do not specify specific conditions in the embodiments are carried out according to conventional conditions or conditions recommended by the manufacturer. Those who do not specify the manufacturer for reagents or instruments used are conventional products that can be purchased commercially. In addition, the terms "first", "second" and "third" are only used for descriptive purposes and cannot be interpreted as indicating or implying relative importance.

[0021] The first aspect of the present invention is to provide a method for preparing high-capacity and high-density lithium iron phosphate.

[0022] (1) An iron source, a phosphorus source, a lithium source, a carbon source, a dispersant, an additive and water are mixed and ground, and spray-dried to obtain a first spray material, wherein the dispersant comprises one of polyurethane, polyaspartic acid or polyol-polyethyleneimine block copolymer.

[0023] (2) The second iron source, the second phosphorus source, the second lithium source, the second carbon source, the second additive and water are mixed and ground, and then spray-dried to obtain a second spray material.

[0024] It is understandable that in steps (1) to (2) of the present invention, two slurries are prepared and their spray materials are obtained respectively; the two slurries have the same selection range in terms of raw material selection range, preparation method, property parameters, etc., and the significant difference lies in whether a dispersant is used. In the present invention, by introducing a dispersant, two precursor dispersions containing a dispersant and not containing a dispersant are obtained in parallel, thereby showing significant differences in the particle size, compacted density, grain state, etc. of the dispersions, and ultimately achieving a significant improvement in electrochemical performance.

[0025] As a preferred embodiment, the iron source and / or the second iron source includes at least one of iron phosphate, iron oxide or iron sulfate; in some more preferred embodiments, the iron source and / or the second iron source includes iron phosphate, and one or both of iron oxide or iron sulfate.

[0026] As a preferred embodiment, the lithium source and / or the second lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium acetate or lithium dihydrogen phosphate; as some typical but non-limiting examples, the lithium source is selected from lithium carbonate, or a combination of lithium carbonate and lithium dihydrogen phosphate, or a combination of lithium hydroxide and lithium dihydrogen phosphate; when a combination of several components is used, the dosage ratio between the components is also not subject to any restrictions.

[0027] As a preferred embodiment, the carbon source and / or the second carbon source includes at least one of sucrose, glucose, polyethylene glycol (PEG), starch or carbon nanotubes.

[0028] As a preferred embodiment, the phosphorus source and / or the second phosphorus source includes at least one of phosphoric acid, lithium dihydrogen phosphate, dihydrogen phosphate or dihydrogen phosphate.

[0029] As a preferred embodiment, the additive and / or the second additive includes a compound containing at least one element of titanium, niobium, vanadium, magnesium or aluminum; it can be understood that each compound additive selected in the present invention usually contains only one element of titanium, niobium, vanadium, magnesium or aluminum, but several compound additives can be selected to provide the corresponding elements of titanium, niobium, vanadium, magnesium or aluminum.

[0030] As an optional embodiment, when the doping and modifying element is titanium (Ti), the additive and / or the second additive includes titanate, titanium dioxide or titanium tetrachloride, etc.; when the doping and modifying element is niobium (Nb), the additive and / or the second additive includes niobium oxide, niobium chloride or niobium acetate, etc.; when the doping and modifying element is vanadium (V), the additive and / or the second additive includes vanadium oxide, vanadium chloride or vanadate, etc.; when the doping and modifying element is magnesium (Mg), the additive and / or the second additive includes magnesium oxide, magnesium hydroxide, magnesium chloride, magnesium carbonate or magnesium nitrate, etc.; when the doping and modifying element is aluminum (Al), the additive and / or the second additive includes aluminum oxide, aluminum hydroxide, aluminum chloride, aluminum nitrate, aluminate, etc.

[0031] As a preferred embodiment, based on the mass of the iron source in each step, the additive and / or the second additive is added in an amount of 1000 ppm to 8000 ppm.

[0032] As a preferred embodiment, in the slurry to be ground in step (1) and step (2), the molar ratio of lithium element, iron element and phosphorus element is 1: (0.95-1): (0.95-1.05). It is worth noting that the molar ratio is for the slurry, not for a single raw material source. In the present invention, it is necessary to macroscopically limit the amount of the integrated element in the raw material source to ensure that the raw material ratio in the lithium iron phosphate contained in each spray material is more accurate, to ensure that the precursor quality is stable and free of impurities, and ultimately to obtain a lithium iron phosphate positive electrode material with excellent electrochemical properties.

[0033] As a preferred embodiment, the mass ratio of the carbon source to the iron source is 3% to 15%, and / or the mass ratio of the second carbon source to the second iron source is 3% to 15%; in some optional embodiments, the mass ratio includes but is not limited to 3%, 4%, 5%, 6%, 7%, 8%, 10%, 11%, 12%, 13%, 14%, 15%, any one of them or a numerical range consisting of any two of them.

[0034] As a preferred embodiment, the solid content of the slurry to be ground in step (1) and step (2) is 20% to 50%, including but not limited to any one of 20%, 25%, 30%, 35%, 40%, 45%, 50% or a numerical range formed by any two of them; it is understandable that those skilled in the art can adaptively adjust the slurry solid content within the above range based on the dispersibility and particle size of the selected raw materials. In some optional cases, before grinding, methods such as oscillation, stirring, centrifugation, ultrasound, etc. can be used to assist in obtaining a uniformly dispersed slurry system.

[0035] As a preferred embodiment, the grinding in step (1) and step (2) is carried out by sand milling, ball milling, vibration milling, etc. It can be understood that mixing the reaction raw materials by first grinding and then spray drying can not only play the role of uniformly mixing the reaction raw materials, but also play the role of refining the particle size of the raw materials, thereby facilitating the uniformity of the lithium iron phosphate particles and the uniform dispersion of the modifying elements in the additive in the positive electrode material.

[0036] As a preferred embodiment, the median particle size of the material after grinding in step (1) and step (2) is 0.3 μm to 0.45 μm, including but not limited to any one of 0.3, 0.32, 0.34, 0.35, 0.36, 0.38, 0.4, 0.41, 0.42, 0.44, 0.45 (μm) or a numerical range consisting of any two of them.

[0037] As a preferred embodiment, in step (1) and step (2), the air inlet temperature of the spray drying is 200°C to 280°C, the air outlet temperature is 80°C to 100°C, and the frequency of the atomizer is 30Hz to 50Hz. In some optional embodiments, the air inlet temperature of the spray drying includes but is not limited to any one of 200, 210, 220, 230, 240, 250, 260, 270, 280 (°C) or a numerical range consisting of any two thereof, and the air outlet temperature includes but is not limited to any one of 80, 82, 85, 88, 90, 92, 95, 98, 100 (°C) or a numerical range consisting of any two thereof.

[0038] As a preferred embodiment, the polyurethane (PU) is formed by polymerization of diisocyanate and diol, contains a carbamate segment (-NHCOO-), and contains a carboxyl group, a sulfonic acid group and an ammonium ion, and is a water-based polyurethane; in some more preferred embodiments, the molecular weight of the polyurethane is 4000 to 8000.

[0039] As a preferred embodiment, the side chain of the polyaspartic acid (PASP) has a carboxylic acid structure, which has an anchoring effect on the group; it has little pollution to the environment and is a green dispersant; in some more preferred embodiments, the molecular weight of the polyaspartic acid is 1000-5000.

[0040] As a preferred embodiment, in the polyol-polyethyleneimine block copolymer, the polyol synthetic monomers used include N,N-dimethylaminopropylamine, octadecylaminopropylamine, diethylethanolamine, etc., containing -R2N, -R3N + Anchoring group.

[0041] As a preferred embodiment, the molecular weight of the polyol-polyethyleneimine block copolymer is 3000-8000.

[0042] As a preferred embodiment, the mass ratio of the dispersant to the iron source is 1% to 5%.

[0043] The dispersant used in the present invention also contains nitrogen, and after subsequent calcination, the dispersant is decomposed into nitrogen-doped carbon wrapped on the surface of lithium iron phosphate. The electronegativity of nitrogen is higher than that of carbon. After nitrogen addition, the electronic structure of carbon can be improved, the conductivity can be improved, and the electrochemical performance of lithium iron phosphate can be improved. At the same time, after the two spray materials with and without the introduction of dispersant are mixed and sintered under the same conditions, higher electrochemical performance can be obtained without changing the temperature or duration.

[0044] Step (3) of the present invention comprises: fully mixing the first spray material and the second spray material, and obtaining lithium iron phosphate after calcining and crushing.

[0045] As a preferred embodiment, when measured at the same metering ratio, the amount of the first spray material is ≤ the amount of the second spray material.

[0046] As a more preferred embodiment, the mass ratio of the first spray material to the second spray material is 1:(1-9), including but not limited to any one of 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9 or a ratio interval consisting of any two of them.

[0047] As a preferred embodiment, the calcination is carried out in a protective atmosphere, and the protective gas used includes but is not limited to one or more of nitrogen, argon, helium or neon.

[0048] As a preferred embodiment, the calcination temperature is 600°C to 800°C, and the calcination time is 7h to 12h; in some optional embodiments, the calcination temperature includes but is not limited to any one of 600, 620, 640, 650, 660, 680, 700, 720, 740, 750, 760, 780, 800 (°C) or a numerical range consisting of any two of them, and the calcination time includes but is not limited to any one of 7, 8, 9, 10, 11, 12 (h) or a numerical range consisting of any two of them.

[0049] In the present invention, the calcination treatment temperature and treatment time are limited to the above ranges respectively. On the one hand, when the temperature is too low, the molecular activity and molecular thermal motion are not obvious enough, so they can only be compensated by the sintering time, which easily leads to a waste of time and energy costs; on the other hand, the molecular activity and molecular thermal motion will be too high, and side reactions between the additive elements and the positive electrode material or overburning of the lithium iron phosphate may occur. Within the above range, calcination can obtain lithium iron phosphate with appropriate compaction density and electrochemical properties.

[0050] As a preferred embodiment, the crushing is carried out by dry grinding, mechanical crushing, or air flow crushing, and more preferably, air flow crushing is used. In some optional embodiments, the frequency of the running motor of the air flow crushing is 20 Hz to 50 Hz, which is sufficient to meet the crushing requirements of lithium iron phosphate and obtain lithium iron phosphate material with suitable crushing fineness.

[0051] As a preferred embodiment, the crushing further includes screening, and the lithium iron phosphate that does not meet the particle size range is removed, or the crushing process is cyclically performed.

[0052] As a preferred embodiment, after the crushing, the particle size of the lithium iron phosphate is 1 μm to 2 μm, and the compaction density of the lithium iron phosphate is greater than 2.5 g / cm 3 .

[0053] As a preferred embodiment, demagnetization is further included after the crushing; the demagnetization is performed by an electromagnetic iron remover. In some optional embodiments, after the demagnetization, the content of magnetic substances in the lithium iron phosphate is less than 1ppm.

[0054] The second aspect of the present invention is to provide lithium iron phosphate prepared by the preparation method of high-capacity and high-density lithium iron phosphate as described in the first aspect.

[0055] A third aspect of the present invention is to provide a lithium ion battery.

[0056] The lithium-ion battery includes the lithium iron phosphate as described in the second aspect. It is understandable that the lithium iron phosphate is the active ingredient of the positive electrode of the lithium-ion battery, or one of the active ingredients of the positive electrode of the lithium-ion battery; the positive electrode of the lithium-ion battery may also include structural elements or functional components such as a conductive agent, a binder, and a current collector; the lithium-ion battery also includes a negative electrode, an electrolyte, a diaphragm, and other necessary or unnecessary functional elements or packaging components, etc., which can be arbitrarily selected and combined by those skilled in the art; when the lithium iron phosphate described in the present invention is included in the lithium-ion battery, it can be regarded as an embodiment of the present invention.

[0057] As a preferred embodiment, the active ingredients of the negative electrode include but are not limited to natural graphite, artificial graphite, silicon-carbon composite materials, soft carbon, hard carbon, lithium titanate, metallic lithium, etc.; the diaphragm includes but is not limited to polyethylene diaphragm, polypropylene diaphragm, polyimide diaphragm, etc.

[0058] A fourth aspect of the present invention is to provide an electrical device.

[0059] The electrical equipment includes the lithium-ion battery. The electrical equipment can be any equipment or device that relies on electric energy to work or operate, including but not limited to new energy vehicles, building electrical equipment, industrial electrical appliances, household and agricultural electrical appliances, etc. When the lithium-ion battery is included, any electrical equipment equipped with the lithium-ion battery can belong to an embodiment of the present invention.

[0060] Example 1

[0061] (1) Weigh 1000 g of iron phosphate, 251 g of lithium carbonate, 30 g of sucrose, 70 g of PEG, 2.5 g of titanium dioxide, 50 g of a 5% polyurethane dispersant (the dispersion solvent is water, and the molecular weight of the polyurethane is 4000) and 2 L of deionized water, add them to a sand mill and grind them for 60 min, then transfer them to a fine grinder and grind them to a D50 of 0.38 μm. The finely ground slurry is spray dried in a spray dryer with an inlet air temperature of 220°C.

[0062] (2) 1000 g of iron phosphate, 251 g of lithium carbonate, 30 g of sucrose, 70 g of PEG, 2.5 g of titanium dioxide and 2 L of deionized water were weighed and coarsely ground in a sand mill for 60 min, and then finely ground in a fine grinder until D50 was 0.41 μm. The finely ground slurry was spray dried in a spray dryer with an inlet air temperature of 220°C.

[0063] (3) The spray materials of step (1) and step (2) were mixed in a ratio of 3:7, calcined at 775° C. for 9 h in a nitrogen atmosphere, and then pulverized and mixed at a pulverization frequency of 45 Hz to obtain the lithium iron phosphate material of this embodiment.

[0064] Example 2

[0065] It is basically the same as Example 1, except that:

[0066] The types of raw materials used in steps (1) and (2) are replaced by: lithium carbonate is replaced by lithium hydroxide, and sucrose is replaced by glucose.

[0067] Example 3

[0068] The process is basically the same as Example 1, except that 2.5 g of titanium dioxide (2.5 / 80=0.03125 mol) in steps (1) and (2) is replaced by 2.44 g of aluminum hydroxide.

[0069] Example 4

[0070] The method is basically the same as Example 1, except that the polyurethane dispersant in step (1) is replaced by polyaspartic acid (molecular weight 3000).

[0071] Example 5

[0072] The method is basically the same as Example 1, except that the polyurethane dispersant in step (1) is replaced by a propylene glycol-polyethyleneimine block copolymer (molecular weight of 5000).

[0073] Example 6

[0074] The method is basically the same as Example 1, except that the spray materials in step (1) and step (2) are mixed in a ratio of 1:1.

[0075] Example 7

[0076] The method is basically the same as Example 1, except that the spray materials in step (1) and step (2) are mixed in a ratio of 1:8.

[0077] Comparative Example

[0078] The method is basically the same as Example 1, except that step (1) is eliminated, and the spray material of step (2) is directly calcined at 775° C. for 9 h under a nitrogen atmosphere, and then pulverized and mixed at a pulverization frequency of 45 Hz to obtain the lithium iron phosphate material of this embodiment.

[0079] Test example

[0080] (1) The compaction density of the lithium iron phosphate prepared in each embodiment and comparative example was tested by a powder tap density meter.

[0081] (2) The lithium iron phosphate prepared in each embodiment and comparative example is configured to obtain a test battery; the lithium iron phosphate prepared in the above embodiments and comparative examples is mixed with conductive carbon black and polyvinylidene fluoride in a mass ratio of 92:4:4, and then mixed with N-methylpyrrolidone to obtain a positive electrode slurry, which is coated on aluminum foil and then baked to obtain a positive electrode; a lithium sheet is used as the negative electrode, a single-layer polypropylene film is used as the separator, EC:DMC:EMC (mass ratio 1:1:1) is used as the solvent, and 1M lithium hexafluorophosphate is added as the electrolyte to prepare a CR2032 coin battery for the test.

[0082] The Land test system was used to test the discharge specific capacity. The test temperature was room temperature, the test voltage range was 2.0-3.75V, and the charging process was first constant current charging to a voltage of 3.75V and then constant voltage charging to 0.05C at 3.75V. The discharge was constant current discharge at 0.1C.

[0083] The test method steps of this test example are provided as shown in Table 1.

[0084] Table 1

[0085]

[0086]

[0087] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.

Claims

1. A method for preparing high-capacity and high-density lithium iron phosphate, characterized in that: The steps include: (1) mixing and grinding an iron source, a phosphorus source, a lithium source, a carbon source, a dispersant, an additive and water, and spray drying to obtain a first spray material; (2) mixing and grinding a second iron source, a second phosphorus source, a second lithium source, a second carbon source, a second additive and water, and spray-drying the mixture to obtain a second spray material; (3) fully mixing the first spray material and the second spray material, calcining and crushing them to obtain lithium iron phosphate; Wherein, the dispersant includes one of polyurethane, polyaspartic acid or polyol-polyethyleneimine block copolymer.

2. The method for preparing high-capacity and high-density lithium iron phosphate according to claim 1, characterized in that: The dispersant comprises at least one of the following characteristics (a) to (c): (a) The molecular weight of the polyurethane is 4000 to 8000; (b) the molecular weight of polyaspartic acid is 1000 to 5000; (c) The molecular weight of the polyol-polyethyleneimine block copolymer is 3,000 to 8,000.

3. The method for preparing high-capacity and high-density lithium iron phosphate according to claim 1, characterized in that: The iron source and / or the second iron source comprises at least one of iron phosphate, iron oxide or iron sulfate; The lithium source and / or the second lithium source comprises at least one of lithium carbonate, lithium hydroxide, lithium acetate or lithium dihydrogen phosphate; The carbon source and / or the second carbon source comprises at least one of sucrose, glucose, polyethylene glycol, starch or carbon nanotubes; The phosphorus source and / or the second phosphorus source includes at least one of phosphoric acid, lithium dihydrogen phosphate, dihydrogen phosphate or dihydrogen phosphate.

4. The method for preparing high-capacity and high-density lithium iron phosphate according to claim 1, characterized in that: The additive and / or the second additive contains at least one element of titanium, niobium, vanadium, magnesium or aluminum; Preferably, the additive and / or the second additive comprises at least one of titanate, titanium dioxide, titanium tetrachloride, niobium oxide, niobium chloride, niobium acetate, vanadium oxide, vanadium chloride, vanadate, magnesium oxide, magnesium hydroxide, magnesium chloride, magnesium carbonate, magnesium nitrate, aluminum oxide, aluminum hydroxide, aluminum chloride, aluminum nitrate or aluminate.

5. The method for preparing high-capacity and high-density lithium iron phosphate according to claim 1, characterized in that: In the slurry to be polished in step (1) and step (2), the molar ratio of lithium element, iron element and phosphorus element is 1: (0.95-1): (0.95-1.05).

6. The method for preparing high-capacity and high-density lithium iron phosphate according to claim 1, characterized in that: The mass ratio of the first spray material to the second spray material is 1:(1-9).

7. The method for preparing high-capacity and high-density lithium iron phosphate according to claim 1, characterized in that: The calcination temperature is 600° C. to 800° C., and the calcination time is 7 h to 12 h.

8. Lithium iron phosphate obtained by the method for preparing high-capacity and high-density lithium iron phosphate according to any one of claims 1 to 7.

9. A lithium ion battery, characterized in that: Comprising the lithium iron phosphate as described in claim 8.

10. An electrical device, characterized in that: Comprising the lithium ion battery as claimed in claim 9.

Citation Information

Cited By

  • High-compaction lithium iron phosphate positive electrode material and preparation method thereof

    CN121076127A